THE EFFECT OF THE IMPLEMENTATION OF ACCOUNTING AND THE USE OF ACCOUNTING INFORMATION ON THE PERCEPTION OF BENEFITS OF ACCOUNTING INFORMATION AN EMPIRICAL STUDY IN BUSINESS MEDIUM IN PALU - Zahra, Femilia; Ika Pertiwi Putri, Wahyuni; Sudirman; Pakawaru, Ilham (Tadulako Social Science and Humaniora Journal, 2020)
This study aims to examine and analyze the effect of the administration and use of accounting information partially and simultaneously on the perception of the benefits of accounting information of medium-sized business actors in the city of Palu. The method used in this research was quantitative by utilizng primary data. The sampling technique used was probability sampling method from which 53 respondents were obtained. The analytical method used was multiple linear regression analysis. The results showed that partially the administration and the use of accounting information significantly influenced the perception of the benefits of accounting information. Simultaneously, the administration and the use of accounting information significantly influences the perception of the benefits of accounting information.